Effects of prolonged exposure to diclofenac sodium on strains of Staphylococcus aureus - A. A. de Lima-e-Silva; R.G. da Silva-Filho; A. S. Viana (Brazilian Journal of Biology)
Abstract Staphylococcus aureus is a pathogen commonly involved in the etiology of nosocomial and community-acquired infections. This microorganism adheres and forms biofilm on biotic and abiotic surfaces, which is a significant complication for infection control. More recently, non-antibiotic medications, such as nonsteroidal anti-inflammatory agents (NSAIDs), have been studied as an alternative for treating infections caused by multidrug-resistant pathogens and infections associated with biofilms. This study assessed the effects of prolonged exposure of S. aureus strains to the NSAID diclofenac sodium regarding biofilm production, direct adhesion, hydrophobicity, susceptibility to antimicrobials, hemolysis, and biochemical profile. Some strains exposed to diclofenac showed increased direct adhesion to hydrophobic and hydrophilic surfaces and increased cell surface hydrophobicity. Two strains, one reference and one clinical, were subjected to repeated and prolonged passages in a culture medium with a diclofenac gradient. In one of them, the drug suppressed biofilm production in the assay with and without subinhibitory concentrations (sub-MICs) from NSAID. Additional repeated passages of this strain in a medium without diclofenac partially recovered the original biofilm-positive phenotype, but only in culture with sub-MICs of the drug. The original characteristics of the strains regarding susceptibility or resistance to antimicrobials and biochemical profile were not affected by prolonged exposure to diclofenac. However, the clinical isolate showed suppressed hemolytic activity.